Effect of job satisfaction on moonlighting intentions: Mediating effectof organizational commitment - Seema; Vikas Choudhary; Garima Saini (European Research on Management and Business Economics (ERMBE), 2021)
Online platform working, Gig working, E lancing and Moonlighting have become synonymous in theIndustry 4.0. Searching for and practicing alternative employments is an important phase in recordingthe sequence of employees' withdrawal cognitions (WC). WC have been studied in the past majorly inrelation with job attitudes for the ultimate consequence of turnover but in this virtual era, it is equallyconsiderable to investigate the relationship of job attitudes with this important cognition sequencedbefore turnover stage, i.e. moonlighting, which may ultimately lead to turnover. This paper proposesto conduit the research gap of investigating the effect of Job Satisfaction on Moonlighting Intentionsand the mediating effect of Organizational Commitment between these two variables. SmartPLS 3.0software has been used to execute partial least squares structural equation modeling (PLS-SEM) forthe research framework on a sample of 161 IT professionals working in the North Indian IT hubs ofN.C.R. Delhi and Chandigarh. In the present study, four hypotheses have been employed for examiningthe relationships among the variables Job Satisfaction, Organizational Commitment and MoonlightingIntentions. PLS -SEM supported all of them. Organizational Commitment has a mediating effect betweenJob Satisfaction & Moonlighting Intentions while Job Satisfaction puts a very high positive impact onOrganizational Commitment. In addition, Organizational Commitment shows a very significant inverselyproportionate relationship with Moonlighting Intentions.
Keywords: M12; M15; M54; J23; 650; Job satisfaction; Organizational commitment; Gig working; PLS-SEM